2014
DOI: 10.5620/eht.2014.29.e2014002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and gene expression of heat shock protein 90 in marine crab <i>Charybdis japonica</i> following bisphenol A and 4-nonylphenol exposures

Abstract: ObjectivesHeat shock protein 90 (HSP90) is a highly conserved molecular chaperone important in the maturation of a broad spectrum of protein. In this study, an HSP90 gene was isolated from Asian paddle crab, Charybdis japonica, as a bio-indicator to monitor the marine ecosystem.MethodsThis work reports the responses of C. japonica HSP90 mRNA expression to cellular stress by endocrine disrupting chemicals (EDCs), such as bisphenol A (BPA) and 4-nonylphenol (NP) using real-time. reverse transcription polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Twelve fish were assessed at each estrogen sampling point. All chemical concentrations were based on previous reports (Atli & Canli, ; Cho et al., ; Park & Kwak, ; Tong et al., ). Fish were sacrificed, and kmWap65‐1 and kmWap65‐2 mRNA patterns were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve fish were assessed at each estrogen sampling point. All chemical concentrations were based on previous reports (Atli & Canli, ; Cho et al., ; Park & Kwak, ; Tong et al., ). Fish were sacrificed, and kmWap65‐1 and kmWap65‐2 mRNA patterns were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies show that HSP genes are upregulated in response to various stresses. For instance, Alexandre et al (2001) (3) found that HSP genes were upregulated in response to ethanol stress, while HSP70 and HSP90 were significantly induced in C. japonica crabs exposed to different inhibitory concentrations of NP (86,87). Furthermore, several stress genes, including HSP12 and HSP26, were significantly upregulated in yeast cells exposed to cadmium (76).…”
Section: High Inhibitory Concentration Of Np Upregulates Genes Encodimentioning
confidence: 99%
“…BPA concentrations observed in U.S. river estuaries were approximately 4 µg L −1 to 21 µg L −1 [12,13]. Exposure to BPA induced transcription responses of the heat shock protein 90 (HSP90) gene in the marine crab Charybdis japonica [14]. Di-(2-ethylhexyl) phthalate (DEHP), a suspected EDC, is widely used as plasticizer and may induce reproductive and developmental toxicities in aquatic environments [15].…”
Section: Introductionmentioning
confidence: 99%